Obesity Prevalence and Related Variables in Children Aged 4-6 Years, Pursaklar Sample - Şefik Yurdakul; Yazgı Beriy Altun Güzelderen; Mehmet Enes Gökler (Güncel Pediatri)
Introduction: Our study aimed to investigate the prevalence of overweight/obesity and factors that may be associated with obesity in preschool children. Materials and Methods: The study is a descriptive cross-sectional study. All children between the ages of 4 and 6 years attending relevant educational institutions were included in the study. The height, weight, waist circumference and hip circumference of 822 children were measured and 556 of the questionnaires were completed and included in the study. Our questionnaire included questions on socio-demographic characteristics and the Quality Index of the Mediterranean Diet in Children(KIDMED scale). The data were analyzed in the SPSS package, and logistic regression models were created with the variables found to be significant after univariate analysis. P≤0.05 was considered statistically significant. Results: Of the participants, 68(12.3%) were overweight and 28(5%) were obese. When analyzing the overweight/obesity status, it was observed that the frequency of being overweight/obese was higher in males(p=0.05), children whose mothers were obese(p<0.001) and children who started complementary feeding before 6 months(p=0.042). In the KIDMED classification, 19.6% of the participants had a high level of compliance and 18% had a low level of compliance. In the logistic regression model, higher maternal Body Mass Index(BMI) increased the risk of obesity status of the participants approximately sevenfold, and switching to complementary foods before 6 months increased the risk approximately threefold. Conclusion: Because the mother is in the most important position in preventing pre-school childhood obesity, maternal health and education should be given importance.